Evaluation of telemedicine for new outpatient neurological consultations. Issue 1 (6th May 2022) - Watila, Musa Mamman; Duncan, Callum; Mackay, Graham
Abstract : Objective: The COVID-19 pandemic has broadened the use of teleneurology, how this compares with face-to-face (F2F) clinics is unclear. This study compared virtual with F2F new neurological consultations. Methods: We retrospectively evaluated new outpatient consultations in neurology clinics in Aberdeen Royal Infirmary. We compared sociodemographic data, time to consultation, time to diagnosis, the need for reassessment and re-investigation between traditional F2F and virtual clinics using the web-based Attend Anywhere platform or telephone into patients' own homes (or chosen location) without a trained assistant. We calculated the relative risk (RR) of the need for reassessment and re-investigation over 6-month periods by the suspected neurological diagnosis. Results: 73% of consultations were virtual ( Attend Anywhere or telephone) between June and October 2020, this was almost non-existent (<0.1%) in June–October 2019. We analysed 352 F2F (June–July 2019) and 225 virtual consultations (June–July 2020). Compared with F2F clinics, virtual clinics had a longer time to diagnosis (p=0.019), were more likely to be reassessed (RR: 2.2, 95% CI: 1.5 to 3.2; p<0.0001) and re-investigated (RR: 1.50, 95% CI: 0.88 to 2.54; p=0.133), this was likelier in those aged ≥60 years. Patients with headaches and suspected seizures were less likely to need reassessment or re-investigation following virtual clinics than multiple sclerosis and neuroinflammatory disorders, spinal cord disorders and functional neurological disorders. Conclusion: This study demonstrates that virtual clinics have higher rates of reassessment and re-investigation than F2F clinics. As virtual clinics become a potential consultation alternative, this study should instruct the selection of patients for either consultation type.